The steady pace of philosophy of colour (Itinera, 2020)
I outline five issues in philosophy of colour that deserve greater attention and provide skeletal frameworks for how future work on these topics could be carried out. The issues are: colour and metaphilosophy (§1), colour and artistic practice (§2), colour and virtual/augmented reality (§3), colour and imagination (§4), and colour and the predictive mind (§5). Some of these issues have been a focus of important recent works. Thus, colour conjoined with each of metaphilosophy, artistic practice and imagination have all been examined in at least a few recent publications – see below for references. It is clear, however, that these recent works are signals that there is much still to be done. By contrast, while at present there is a great deal of interest in the predictive mind, the intersection of colour and the predictive mind is vastly underexplored. This is despite the fact that the philosophy and science of colour are rather developed disciplines. Finally, while there have been some very important recent works on virtual and augmented reality, the significance of colour for these studies has yet to be examined. It is my hope that after reading this article readers are convinced not only that the philosophy of colour has a rich, recent history, but also a very bright future.